2020
DOI: 10.2147/rru.s267417
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Functional Bladder Capacity in Children with Nocturnal Enuresis According to Type and Treatment Outcome</p>

Abstract: This study aimed to identify whether functional bladder capacity (FBC) differs among subgroups of nocturnal enuresis (NE) patients and can be used to predict treatment response. Methods: A total of 69 children with NE were included in this study between July 2017 and February 2019 according to medical chart review, retrospectively. All patients completed a questionnaire about voiding symptoms and 48-hour frequency/volume (48-h F/V) charts. FBC was obtained from the 48-h F/V charts and uroflowmetry (UFM) with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Children with NE have diminished functional bladder capacity and detrusor instability, which may be due to delayed maturation of the bladder and its functional controlling signal pathways. 2 , 39 It is also known that the bladder contributes to nocturia in the case of low capacity, urgency, and detrusor overactivity. 37 , 40 An inability to hold urine at night and uninhibited bladder contractions may result from issues in bladder development, which begin in childhood and carry on into adulthood, resulting in NE, then nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…Children with NE have diminished functional bladder capacity and detrusor instability, which may be due to delayed maturation of the bladder and its functional controlling signal pathways. 2 , 39 It is also known that the bladder contributes to nocturia in the case of low capacity, urgency, and detrusor overactivity. 37 , 40 An inability to hold urine at night and uninhibited bladder contractions may result from issues in bladder development, which begin in childhood and carry on into adulthood, resulting in NE, then nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…6 EBC can be calculated from the Koff formula (bladder capacity=(age in year+2)×30), which is used for children 4-12 years old, and the result of this formula is in milliliters. 33 The laboratory evaluation besides a urinalysis is usually unnecessary since this test will show a low specific gravity in diabetes insipidus, glycosuria in case of diabetes mellitus, and the presence of nitrites leukocyte esterase, leukocytes, or bacteria in case of infection. 19 There is no indication for the use of imaging techniques or urodynamic studies except in cases that patients are NMNE or do not respond to initial treatment.…”
Section: Diagnosismentioning
confidence: 99%
“…Maternik et al [ 1 ] reported no significant difference between the FBC obtained from the 48-h F/V chart and that obtained from uroflowmetry with PVR in patients with several LUTS. Kang et al [ 2 ] also reported a lack of significant variance in FBC values obtained from the two measurement methods.…”
Section: How Is Functional Bladder Capacity Measured In Children With...mentioning
confidence: 99%
“…In the study by Liu et al [ 4 ], 33.9% of children with MNE had a low bladder capacity. Kang et al [ 2 ] reported that 68% to 70% of patients (according to measurement method) had a small FBC for age, regardless of NE subgroup. Baek et al [ 5 ] found that the prevalence of reduced bladder capacity without daytime voiding symptoms was relatively high (27.8%) in children newly diagnosed with primary NE.…”
Section: Functional Bladder Capacity As a Predictor Of Treatment Outc...mentioning
confidence: 99%